The improvement of understanding the concept of building space through prodigy-based digital educational games with an instructional learning model - Syaripudin, Ahmad; Prastowo, Andi; Noor Auliya Huda (Desimal: Jurnal Matematika, 2025)
Mathematics learning at the Madrasah Ibtidaiyah level still faces various challenges, such as students' lack of understanding of basic mathematical concepts and their low motivation in following lessons. One of the contributing factors is the limited learning methods and strategies applied. This study aims to explore the application of the Instructional Games model through the use of Digital Game-Based Learning (DGBL) technology, especially by using the Prodigy website, in improving students' understanding of mathematics. The research method used is qualitative, with an in-depth interview approach to obtain data. The results of the study indicate that the use of Prodigy as part of Digital Game-Based Learning (DGBL) is effective in improving students' understanding of mathematical concepts and improving their learning engagement and motivation. These findings suggest that schools, especially Madrasah Ibtidaiyah, consider integrating DGBL into mathematics learning to improve students' understanding and collaboration skills.